Real-time image fusion and Apple Vision Pro in laparoscopic microwave ablation of hepatic hemangiomas - Tao Lan; Sichun Liu; Yihe Dai; Jia Luo; Jiang Han; Yun Jin (npj Precision Oncology)
Abstract Laparoscopic ultrasound-guided liver microwave ablation requires precise navigation and spatial accuracy. We developed an image fusion navigation system that integrates laparoscopic, ultrasound, and 3D liver model images into a unified real-time visualization. The Apple Vision Pro mixed reality device projects all essential image information into the surgeon’s field of view in real-time. This system reduces cognitive load and enhances surgical precision and efficiency. Comparative experiments showed a significant improvement in puncture accuracy under AVP guidance (success rate of 90%) compared to traditional methods (42.5%), benefiting both novice and experienced surgeons. According to the NASA Task Load Index evaluation, the system also reduced the workload of surgeons. In eight patients, ablation was successful with minimal blood loss, no major complications, and rapid recovery. Despite challenges such as cost and fatigue, these results highlight the potential of mixed reality technology to improve spatial navigation, reduce cognitive demands, and optimize complex surgical procedures.